ANALISIS STANDAR SARANA DAN PRASARANA DALAM MENINGKATKAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (Studi Kasus MTs Nurul Huda Kabupaten Tasikamalaya) - Mumu; Heni Nuraidah (Program Studi Pendidikan Agama Islam, 2023)
The purpose of this research is to know the facilities and infrastructure at MTs Nurul Huda, Tasikmalaya Regency. Knowing the learning of Islamic Religious Education at MTs Nurul Huda, Tasikmalaya Regency. Knowing the analysis of standard advice and infrastructure in improving the learning of Islamic Religion Educators at MTs Nurul Huda, Tasikmalaya Regency. The method used in this research is descriptive method with a qualitative approach. The data collection techniques used in this study are observation, interview and documentation techniques. The results of the study show that learning in the field of Islamic Religious Education at Madrasah Tsanawiyah includes: Al-Qur'an Hadith, Arabic Language, Aqidah Akhlak, and Islamic Cultural History. As for the analysis of the standard of infrastructure in the learning of Islamic Religious Education, namely as follows: religious infrastructure, laboratories and libraries of Islamic Religious Education. At MTs Nurul Huda, Tasikmalaya Regency, it can be categorized as inadequate and incomplete in terms of facilities and infrastructure in supporting the process of teaching and learning activities, especially for Islamic Religious Education subjects. This is due to the unavailability of facilities such as laboratories and libraries for Islamic Religious Education.